Western European ecological data - Austria - Ersson, Svante (Umeå University, 1991)
This study includes data on regional level for nine Western European countries: election returns, occupation categories, religion, population.

This study includes data on regional level for nine Western European countries: election returns, occupation categories, religion, population.

Data from Austria.
Västeuropeiska ekologdata - Österrike
Keywords: DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Employment; Sysselsättning; Elections; Val; Religion and values; Religion och värderingar; Social Sciences; Samhällsvetenskap